SECONDARY STUDENTS’ EXPERIENCES IN WRITING NARRATIVE TEXT ASSISTED BY ANIMATION MOVIE - Astri Listiani; Iwan Ridwan (PROJECT (Professional Journal of English Education), 2022)
Many of the students have difficulty in the ability to write good and correct English. The difference between English and mother tongue leads to an inability to choose words in the writing process. Furthermore, due to the lack of student motivation, students' interest in writing, specifically in writing narrative texts, is relatively low. Therefore, the use of film animation media can be applied to assist students in writing narrative text in English classes. This research uses a qualitative method, data collection is collected by interview that aims to find out students' experiences in the process of writing narrative texts that are assisted by animated movie media. The study participants were 11th graders from a public school in Karawang who were selected about 18 students. The results revealed that students feel the use of animated film media is an effective medium for teaching and learning to write narrative text. In addition, most of them are happy and motivated during the learning process. Keywords:  Writing Skill, Narrative Text, Animation Movie